INFORMATION SYSTEM FOR MAINTAINING THE REGISTER OF CLIENTS OF THE BANK - ZELINSKA, OKSANA; POTAPOVA, NADIIA; YEMELIANOVA, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The information system (IS) is designed to collect, transmit, process, store, and provide information needs of users. An information system consists of people, equipment, processes, procedures, data, and operations. Today, many systems already exist and are being created, the purpose of which is simple management, and easy and accessible provision of all the necessary information that the user wants. Each information system is created to fulfill a given task in the field of its application. All of them are different, and unique, and have many different functions that can be not only useful but also sometimes redundant. An information system, in simple words, is a large reference book on a certain topic, but in an electronic version, in which any person can easily find what he needs without much effort. Therefore, the relevance of the article lies in the creation of a highly specialized, simple, and intuitive information system without overloading with unnecessary information, which in the future will be able to compete with already existing systems of a similar nature. The purpose of the article is a detailed study of the processes that take place at each stage of the development of an information system up to the moment of its software implementation, as well as the creation of such an information system that can be easily worked with without undue effort. An information system is also an important tool for performing management functions. Therefore, the study of the processes of creating an information system will take place on the example of creating an information system for maintaining a register of bank clients. The article outlines the tasks that must be completed to achieve the goal. Besides the article examines in detail the process of analysis and development of an information system in the form of conceptual and logical models. Also, for a better understanding of the processes, the research results are visually presented in the form of tables and diagrams.